Toxicity of Dimorphandra mollis to Workers of Apis mellifera - Cintra, Priscila [UNESP]; Malaspina, Osmar [UNESP]; Petacci, Fernando; Fernandes, João B.; Bueno, Odair C. [UNESP]; Vieira, Paulo C.; Silva, M. Fátima das G. F. da (Sociedade Brasileira de Química, 2002)
Nesta comunicação estamos reportando as propriedades tóxicas dos extratos metanólicos das flores, pedúnculos, folhas, pecíolo e casca do tronco de Dimorphandra mollis sobre as operárias de Apis mellifera. Astilbina (3-beta-O-rhamnosideo de 5,7,3',4'-- tetraidroxi-2,3-diidroflavonol) isolada dos pedúnculos e flores como o seu principal componente, apresentou atividade inseticida sobre abelhas confinadas. Os resultados obtidos indicam que a astilbina reduz a sobrevivência média das abelhas tratadas.

In this communication we have evaluated the toxic properties of methanol extracts from flowers, peduncles, leaves, petioles and stem bark of Dimorphandra mollis to Apis mellifera workers. Astilbin (5,7,3',4'-tetrahydroxy--2,3-dihydroflavonol-3-beta-O-rhamnoside) has been isolated from peduncles and flowers of this plant in large amounts. Astilbin presented insecticidal activity against confined bees. The results suggest that astilbin reduces the average survival of treated bees.
Keywords: flavonoids; natural insecticides; Dimorphandra mollis; Apis mellifera